0663 Impact of Continuous Positive Airway Pressure (CPAP) Therapy of Obstructive Sleep Apnea (OSA) on occurrence of Periodic Limb Movements of Sleep (PLMS). (27th April 2018) - Budhiraja, R; Epstein, L; Pavlova, M; Batool-Anwar, S; Javaheri, S; Omobomi, O S; Quan, S F
Abstract: Introduction: The relationship between CPAP therapy and PLMS in OSA patients is unclear. Our aims were to assess whether the presence of PLMS represents an incomplete resolution of breathing abnormalities by measuring whether CPAP therapy improves or worsens the PLM index (PLMI). Methods: We analyzed data from the Apnea Positive Pressure Long-term Efficacy Study (APPLES), a prospective 6-month multicenter trial of 1105 subjects with OSA randomized to active or sham CPAP. The participants underwent a baseline polysomnogram (PSG) followed by a titration PSG and follow up PSGs at 2-, 4- and 6-months. 558 were randomized to active CPAP. The change in PLMI from the titration study to the 6-month follow up study was compared between the CPAP and sham control groups to assess whether CPAP therapy worsens PLMI Results: 19.7% of all participants had PLMI ≥ 10/hour. There was no correlation between PLMI and residual AHI on the titration study (R=-0.07, P=0.45). There was no difference between the CPAP and sham groups in baseline PLMI (7.2 ± 16.6 vs. 6.4 ± 13.7, P=0.4) or the mean change in PLMI from baseline to 6 months (3.0 ± 16.6 vs. 2.2 ± 15.9, P=0.5). Similar proportions of those started on CPAP versus those on sham had PLMI≥25/hour at baseline (9.5% vs. 9.1%, P=0.9) and at 6-months (14.7% vs. 11.3%, P=0.15). In the CPAP group, 52.2% had same or higher PLMI at 6 months compared to baseline versus 47.8% in the sham group (P=1.0). Among those with a baseline PLMI≥ 10/hour, there was a similar decline in PLMI in both CPAP and sham groups at 6 months (-4.2 ± 25.4 vs. -4.8 ± 25.0, P=0.9) in all participants and also specifically in participants with adherence > 4 hours/ night (-4.3 ± 25.8 vs. -8.3 ± 25.1, P=0.4). Conclusion: PLM occurrence was not suggestive of incomplete resolution of breathing abnormalities. We did not find any change in PLMS with CPAP therapy. Support (If Any): NHLBI contract 5UO1-HL-068060.